2012
DOI: 10.3748/wjg.v18.i38.5338
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical basis of a beneficial role for vitamin D in viral hepatitis

Abstract: Abnormal bone metabolism and dysfunction of the calcium-parathyroid hormone-vitamin D axis have been reported in patients with viral hepatitis. Some studies suggested a relationship between vitamin D and viral hepatitis. Genetic studies have provided an opportunity to identify the proteins that link vitamin D to the pathology of viral hepatitis (i.e., the major histocompatibility complex class II molecules, the vitamin D receptor, cytochrome P₄₅₀, the renin-angiotensin system, apolipoprotein E, liver X recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 196 publications
0
7
0
Order By: Relevance
“…Administration of calcitriol, however, prevents ER stress [ 28 ]. Vitamin D alters apo levels such as apoA1 and apoE [ 21 ], otherwise apoJ impedes vitamin D signaling pathway [ 23 , 24 ]. Instead, the modulation of apo levels are essential for HCV production, assembly and secretory machinery [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of calcitriol, however, prevents ER stress [ 28 ]. Vitamin D alters apo levels such as apoA1 and apoE [ 21 ], otherwise apoJ impedes vitamin D signaling pathway [ 23 , 24 ]. Instead, the modulation of apo levels are essential for HCV production, assembly and secretory machinery [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of interest at the pathogenesis of HCV infection includes virus infection, lipid metabolism [ 8 ], oxidative and nitrative stress [ 9 , 10 , 11 ], endoplasmic reticulum (ER) stress [ 11 , 12 , 13 ], ER-associated degradation (ERAD) pathway [ 14 ] and host anti-viral signals [ 11 , 15 ]. Previous studies also indicate that vitamin D or calcitriol regulates lipid metabolism [ 16 , 17 , 18 , 19 , 20 ], affects apolipoprotein (apo) and cholesterol levels [ 21 , 22 , 23 , 24 ], prevents nitrative stress [ 25 ] and ER stress [ 26 , 27 , 28 ] and negatively modulates peroxisome proliferator-activated receptor (PPAR)-related signals [ 17 , 20 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, many authors have suggested that the reason for hyperparathyroidism in such patients is the decrease of vitamin D level [67,68]. Previous studies have shown that the lowest normal calcidiol levels, at which PTH secretion is minimal, is on average 40 ng/mL [62,69]. Among participants in our study, in all the samples taken during the day, the concentrations of (25(OH)D) levels were below the designated threshold.…”
Section: Prace Oryginalnementioning
confidence: 60%
“…Investigation of the beneficial role of vitamin D in HBV infection was first reported by Luong and Nguyen,19 and several other studies followed thereafter. Some of the subsequent studies have showed a lower level of vitamin D3 in patients with chronic HBV (CHB), and these have mainly been presented during the most recent years.…”
Section: Introductionmentioning
confidence: 99%